The Relationship Between Learning Motivation and Academic Achievement of High School Students - Abdul Sofyan; Muhamad Fadli; Elieser Kulimbang; Hasan; Erlis Warti (Gateway for Understanding Research in Education, 2025)
This study investigated the significant relationship between learning motivation and academic achievement among high school students across the diverse educational landscape of Indonesia. Recognizing motivation as a core psychological determinant (Setyadi et al., 2021), the research aimed to quantify the association between these two key variables. Employing a quantitative correlational design, data were systematically collected from a nationally representative sample of 605 students (N = 605) from various regions, ensuring adequate representation across geographic and socio-economic strata. Data sources included standardized motivation questionnaires and official academic records (report card averages).The findings reveal a positive and statistically significant correlation (r = 0.41, p < 0.05) between learning motivation and academic achievement, indicating that higher levels of motivation are moderately yet strongly associated with superior academic outcomes. Further analysis demonstrated that learning motivation accounts for approximately 17%  of the variance in student achievement. The analysis of mean scores confirmed this trend, showing that highly motivated students achieved substantially higher average grades (87.2) compared to students with low motivation ( 74.5). The study concludes that fostering students' intrinsic motivation through supportive home and school environments consistent with the tenets of Self Determination Theory (Deci & Ryan, 2012) is essential for enhancing academic success in secondary education. These results provide critical, evidence-based direction for targeted interventions in educational practice and policymaking in Indonesia.